Research and Development (R&D), Environmental Investments, to Eco-Efficiency, and Firm Value - Vera Apridina Safitri; Lindriana Sari; Rindu Rika Gamayuni (The Indonesian Journal of Accounting Research, 2020)
This study aims to determine the relation between research and development (R&D) investment and environmental investment to eco-efficiency and firm value in manufacturing, plantation and mining companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The results of this study show research and development (R&D) investment has a positive and significant correlation to eco-efficiency and firm value it shows that research and development (R&D) investment is very important to improve eco-efficiency and firm value, while environmental investment has no correlation with eco-efficiency and firm value. In addition, this study shows that there is no relation between eco-efficiency and firm value. Based on this result, it is known that investment in the environment has not been a concern for entrepreneurs and investors, therefore strict regulations for business people are needed regarding topreserve the environment. Meanwhile, accounting standards are needed in accordance with Indonesia’s conditions which require companies to disclose financial statements related to the environment transparently.This study aims to determine the relation between research and development (R&D) investment and environmental investment to eco-efficiency and firm value in manufacturing, plantation and mining companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The results of this study show research and development (R&D) investment has a positive and significant correlation to eco-efficiency and firm value it shows that research and development (R&D) investment is very important to improve eco-efficiency and firm value, while environmental investment has no correlation with eco-efficiency and firm value. In addition, this study shows that there is no relation between eco-efficiency and firm value. Based on this result, it is known that investment in the environment has not been a concern for entrepreneurs and investors, therefore strict regulations for business people are needed regarding topreserve the environment. Meanwhile, accounting standards are needed in accordance with Indonesia’s conditions which require companies to disclose financial statements related to the environment transparently.